2021
DOI: 10.1016/j.euo.2021.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Cell-free and Circulating Tumor DNA in Kidney and Bladder Cancer: A Critical Review of Current Literature

Abstract: Context: Bladder and kidney cancers require invasive procedures for definitive diagnosis, and bladder cancer requires repeated procedures to monitor for disease recurrence. Given the recent work to identify molecular alterations in liquid biopsies to diagnose and monitor these diseases, a synthesis of the growing body of evidence is merited. Objective: To review current data on cell-free DNA (cfDNA) and circulating tumor DNA (ctDNA) and to synthesize their roles in the diagnosis, monitoring, and prognosticatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 64 publications
0
24
0
2
Order By: Relevance
“…In addition, previous studies of the fragmentation patterns, copy number aberration, DNA mutation, methylation, integrity and concentrations of urinary cfDNA revealed that urinary cfDNA has emerged as an informative biomarker for prenatal screening, organ transplantation monitoring and infectious/urological malignant disease diagnosis. 3 , 8 , 9 , 10 , 11 , 12 , 13 …”
Section: Introductionmentioning
confidence: 99%
“…In addition, previous studies of the fragmentation patterns, copy number aberration, DNA mutation, methylation, integrity and concentrations of urinary cfDNA revealed that urinary cfDNA has emerged as an informative biomarker for prenatal screening, organ transplantation monitoring and infectious/urological malignant disease diagnosis. 3 , 8 , 9 , 10 , 11 , 12 , 13 …”
Section: Introductionmentioning
confidence: 99%
“…The role of ctDNA to predict and monitor treatment response in kidney cancer has also been evaluated [ 90 ]. In a recent study, genomic alterations in ctDNA were evaluated in 220 patients with metastatic RCC.…”
Section: Circulating Biomarkers In Metastatic Rccmentioning
confidence: 99%
“…Letztlich unterliegen Primärtumore und Metastasen bedingt durch verschiedene Therapien einer klonalen Evolution. Publizierte Diskrepanzen zwischen Primärtumor und ctDNA sind darüber hinaus durch unterschiedliche Plattformen, die für die Sequenzierung verwendet wurden, verursacht, sodass ein direkter Vergleich nur bedingt möglich ist [9]. Dagegen sequenzierten Vandekerhove et al 265 Gene in gematchten Tumorgeweben und ctDNA von 46 metastasierten Patienten auf derselben Plattform [10].…”
Section: Zirkulierende Tumorzellenunclassified
“…In Abhängigkeit von den Plattformen und Genpanels wurde in 73-90% der Patienten mit metastasierten Urothelkarzino-men ctDNA durch NGS nachgewiesen [9]. Dagegen war die Rate bei Patienten mit organbegrenzten Tumoren wesentlich niedriger (14%) [11].…”
Section: Zirkulierende Tumorzellenunclassified